PERLUASAN MAKNA BUSHU HEN BERBENTUK æ—¥(HI-HEN) - Putri, Nurefni Indah; Aibonotika, Arza; Budiani, Dini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is a study of the expansion of the meaning of kanji which has bushu æ—¥(hi). This study aims to facilitate the classification of the kanji based on the form of the expansion of the meaning. This research using descriptive method by describe the origin of kanji and expansion of meaning in the kanji that has bushu æ—¥(hi). this study using the rikusho theory to determmine the origin of each kanji, then determine how the shape of the expansion that occors in each kanji. Based on the rikusho theory and determination of the expansion of meaning, the writer concloudes that the kanji that has bushuæ—¥(hi) generally expansion of meaning to belong the category of meaning expansion from concrete to abstract.Keywords: Expansion of Meaning, Kanji, Bushu, Rikusho, Hi